2016
DOI: 10.1007/s11606-016-3590-9
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Chronic Conditions, Functional Limitations, and Geriatric Syndromes that Predict Health Outcomes

Abstract: BACKGROUND:The strategic framework on multiple chronic conditions released by the US Department of Health and Human Services calls for identifying homogeneous subgroups of older adults to effectively target interventions aimed at improving their health. OBJECTIVE: We aimed to identify combinations of chronic conditions, functional limitations, and geriatric syndromes that predict poor health outcomes. DESIGN, SETTING AND PARTICIPANTS Data from the 2010-2012 Health and Retirement Study provided a representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 21 publications
1
80
0
3
Order By: Relevance
“…Impaired mobility is highly prevalent and is associated with more than double the risk of mortality among older adults 16. In fact, functional limitations have been shown to be a stronger predictor of mortality than chronic conditions 14. Nineteen studies were identified that examined the relationship between ST and function, with a variety of outcomes used to represent ‘function’.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired mobility is highly prevalent and is associated with more than double the risk of mortality among older adults 16. In fact, functional limitations have been shown to be a stronger predictor of mortality than chronic conditions 14. Nineteen studies were identified that examined the relationship between ST and function, with a variety of outcomes used to represent ‘function’.…”
Section: Methodsmentioning
confidence: 99%
“…They found a graded increase in hazard ratios for all-cause mortality with each additional condition that was present 16. Recently, Koroukian et al 14 examined the combinations of chronic conditions, functional limitations and geriatric syndromes that predict poor health in older adults. Using a representative sample of more than 16 000 older adults, they showed that functional limitations and geriatric syndromes were stronger predictors of poor self-reported health and 2-year mortality than the presence of chronic conditions such as diabetes or heart disease 14.…”
Section: Introductionmentioning
confidence: 99%
“…Idosos jovens com ≥68,5 anos, com dificuldade para caminhar várias quadras, sintomas depressivos e má APS apresentavam o risco para piora da APS em dois anos. Já, longevos com ≥ 80,5 anos, apresentando limitações tanto em ABVD como em AIVD, tinham aumento do risco para morte em dois anos (KOROUKIAN et al, 2016).…”
Section: Artigos Originais -Promoção Da Saúdeunclassified
“…No entanto, o estudo de Koroukian et al (2016) encontrou maiores percentuais de baixa APS e piora da mesma em dois anos, principalmente nas limitações em ABVD, onde 76 dos indivíduos com limitação em ABVD tinham pior APS, ao passo que 65 daqueles com prejuízo das AIVD concorriam com esse declínio. Nesta pesquisa, observamos médias de independência em ABVD, maiores do que as de AIVD, e AIVD teve maior correlação com a APS do que ABVD.…”
Section: Artigos Originais -Promoção Da Saúdeunclassified
“…Several studies suggested that chronic conditions and geriatric syndromes interacted synergistically with respect to their association with health outcomes among older adults [9], but others revealed that morbidity might be less informative for outcome prediction than geriatric syndromes [10]. The controversy in results from the existing literature may be related to the accuracy of the comorbidity of interest.…”
Section: Introductionmentioning
confidence: 99%